2016
DOI: 10.1182/blood-2015-10-673103
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic crosstalk with endothelial cells expands murine mesenchymal stromal cells

Abstract: Key Points• tPA expands mesenchymal stromal cells (MSCs) in the bone marrow by a cytokine (KitL and PDGF-BB) crosstalk with endothelial cells.• Pharmacologic inhibition of receptor tyrosine kinases (c-Kit and PDGFRa) impairs tPA-mediated MSC proliferation.Tissue plasminogen activator (tPA), aside from its vascular fibrinolytic action, exerts various effects within the body, ranging from synaptic plasticity to control of cell fate. Here, we observed that by activating plasminogen and matrix metalloproteinase-9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Moreover, it has recently been shown that some fibrinolysis associated factors can also play an indirect role in HSC regulation by creating a more supportive microenvironment. For example, tissue plasminogen activator (tPA) has been demonstrated to induce the expansion of CD45 − TER119 − Sca‐1 + PDGFRα + mesenchymal stromal cells (PαS MSCs) in BM [Dhahri et al, ]. Mechanistically, tPA induces the release of kit ligand from PαS MSCs which activates c‐kit + endothelial cells to secrete platelet derived growth factor‐BB and fibroblastic growth factor‐2.…”
Section: Soluble Factors and Surface Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has recently been shown that some fibrinolysis associated factors can also play an indirect role in HSC regulation by creating a more supportive microenvironment. For example, tissue plasminogen activator (tPA) has been demonstrated to induce the expansion of CD45 − TER119 − Sca‐1 + PDGFRα + mesenchymal stromal cells (PαS MSCs) in BM [Dhahri et al, ]. Mechanistically, tPA induces the release of kit ligand from PαS MSCs which activates c‐kit + endothelial cells to secrete platelet derived growth factor‐BB and fibroblastic growth factor‐2.…”
Section: Soluble Factors and Surface Proteinsmentioning
confidence: 99%
“…Mechanistically, tPA induces the release of kit ligand from PαS MSCs which activates c‐kit + endothelial cells to secrete platelet derived growth factor‐BB and fibroblastic growth factor‐2. As a positive feedback, PDGFRα expression is upregulated in PαS MSCs ultimately leading to cell expansion [Dhahri et al, ].…”
Section: Soluble Factors and Surface Proteinsmentioning
confidence: 99%
“…Propidium iodide fluorescence was measured and positive cells (dead cells) were excluded. MSC isolation and culture from bone marrow cells were performed, as described by Dhahri et al (27).…”
Section: Msc Analysismentioning
confidence: 99%
“…The tumor niche is recognized as a key factor in the multiple stages of cancer progression, mediating local resistance, immune escape, and metastasis (26). We showed that tPA can expand platelet-derived growth factor receptor (PDGFR) a-MSCs in noncancerous tissues (27).…”
mentioning
confidence: 99%
“…1 T he bone marrow (BM) preserves long-term repopulating hematopoietic stem cells (LT-HSCs) for life-long blood cell production and immunity. Hematopoietic stem cells (HSCs) reside predominantly in perivascular niches formed by sinusoidal endothelial and mesenchymal cells.…”
Section: Wolfram Ruf Center For Thrombosis and Hemostasis Mainzmentioning
confidence: 99%